The Psychology of Dilemmas and the Philosophy of Morality. - Cushman, Fiery; Young, Liane (Ethical Theory & Moral Practice, 2009)
We review several instances where cognitive research has identified distinct psychological mechanisms for moral judgment that yield conflicting answers to moral dilemmas. In each of these cases, the conflict between psychological mechanisms is paralleled by prominent philosophical debates between different moral theories. A parsimonious account of this data is that key claims supporting different moral theories ultimately derive from the psychological mechanisms that give rise to moral judgments. If this view is correct, it has some important implications for the practice of philosophy. We suggest several ways that moral philosophy and practical reasoning can proceed in the face of discordant theories grounded in diverse psychological mechanisms.